Climate overtakes vegetation greening in regulating spatiotemporal patterns of soil moisture in arid Central Asia in recent 35 years - Nigenare Amantai; Yuanyuan Meng; Jingzhe Wang; Xiangyu Ge; Zhiyao Tang (GIScience & Remote Sensing)
Satellite datasets have revealed significant greening and soil drying in arid Central Asia. However, the influence mechanism of vegetation and climate on soil moisture dynamics is still unclear. In this study, we investigated the spatiotemporal consistency of vegetation and soil moisture changes, examined the controlling factors of soil moisture under different vegetation indices (normalized differential vegetation index, NDVI; leaf area index, LAI), and explored the time lag and accumulation effects of vegetation greening on the soil moisture in arid Central Asia in the period of 1985 to 2020. The results showed that the co-occurrence of vegetation greening and soil drying in 30.4% (NDVI) and 19.4% (LAI) of the study area spatially. Temporally, the soil moisture increased from 1985 to 1989, but decreased from 1989 or 1990 to 2020. In contrast, vegetation activity increased continuously during 1985–2020. Precipitation accounted for the most variance of the soil moisture. The vegetation greenness demonstrated positive correlations with soil moisture, representing 20.7% (for NDVI) and 39.3% (for LAI) of vegetated areas (areas with long-term mean NDVI ≥ 0.1 and LAI > 0), while negative correlations were observed in only 5.4% (for NDVI) and 3.3% (for LAI) of vegetated areas, respectively. Soil moisture exhibited varying time lag and accumulation effects in response to different vegetation indices, precipitation, and temperature. The main temporal effects of NDVI and temperature were simultaneous changes with no time lag or accumulation effects on soil moisture. In contrast, the main temporal effects of LAI and precipitation included 1-month lag in their influence on soil moisture. Considering the inconsistencies in spatiotemporal patterns between vegetation and soil moisture, as well as the dominance and time lag effects of precipitation on soil moisture variations, we concluded that climate, especially precipitation, rather than vegetation greening, regulates soil moisture in Central Asia. These findings provide a scientific basis for vegetation restoration or regional water resource management in drylands.